The Skeletal-Protecting Action and Mechanisms of Action for Mood-Stabilizing Drug Lithium Chloride: Current Evidence and Future Potential Research Areas - Wong, Sok Kuan; Chin, Kok-Yong; Ima-Nirwana, Soelaiman (Frontiers in Pharmacology, 2020)
Lithium, the lightest natural-occurring alkali metal with an atomic number of three, stabilizes the mood to prevent episodes of acute manic and depression. Multiple lines of evidence point to lithium as an anti-suicidal, anti-viral, anti-cancer, immunomodulatory, neuroprotective and osteoprotective agent. This review article provides a comprehensive review of studies investigating the bone-enhancing effects of lithium and its possible underlying molecular mechanisms. Most of the animal experimental studies reported the beneficial effects of lithium in defective bones but not in healthy bones. In humans, the effects of lithium on bones remain heterogeneous. Mechanistically, lithium promotes osteoblastic activities by activating canonical Wingless (Wnt) / beta (β)-catenin, phosphatidylinositol 3-kinase (PI3K) / protein kinase B (Akt) and bone morphogenetic protein-2 (BMP-2) transduction pathways but suppresses osteoclastic activities by inhibiting the receptor activator of nuclear factor-kappa B (RANK) / receptor activator of nuclear factor-kappa B ligand (RANKL) / osteoprotegerin (OPG) system, nuclear factor-kappa B (NF-κB), mitogen-activated protein kinase (MAPK) and calcium signalling cascades. In conclusion, lithium confers protection to the skeleton but its clinical utility awaits further validation from human clinical trials.